Targeting PYK2, entrectinib allays anterior subcapsular cataracts in mice by regulating TGFβ2 signaling pathway - Xuefei Ding; Xiaohe Li; Rui Fang; Peilin Yue; Yuxuan Jia; Enjie Li; Yayue Hu; Honggang Zhou; Xudong Song (BMC, 2024)
Abstract Background Fibrosis cataract occurs in patients receiving cataract extraction. Still, no medication that can cure the disease exists in clinical. This study aims to investigate the effects and mechanisms of Entrectinib on fibrotic cataract in vitro and in vivo. Methods The human lens cells line SRA 01/04 and C57BL/6J mice were applied in the study. Entrectinib was used in animals and cells. Cataract severity was assessed by slit lamp and Hematoxylin and Eosin staining. Expression of alpha-smooth muscle actin, fibronectin, and collagen I were examined by real-time quantitative PCR, western blotting, and immunofluorescence. Cell proliferation was evaluated by Cell Counting Kit-8. Cell migration was measured by wound healing and transwell assays. Molecular docking, Drug Affinity Responsive Target Stability, and Cellular Thermal Shift Assay were applied to seek and certify the target of Entrectinib treating fibrosis cataract. Results Entrectinib can ameliorate fibrotic cataract in vitro and in vivo. At the RNA and the protein levels, the expression of alpha-smooth muscle actin, collagen I, and fibronectin can be downgraded by Entrectinib, while E-cadherin can be upregulated. The migration and proliferation of cells were inhibited by Entrectinib. Mechanistically, Entrectinib obstructs TGFβ2/Smad and TGFβ2/non-Smad signaling pathways to hinder the fibrosis cataract by targeting PYK2 protein. Conclusions Targeting with PYK2, Entrectinib can block TGF-β2/Smad and TGF-β2/non-Smad signaling pathways, lessen the activation of EMT, and alleviate fibrosis cataract. Entrectinib may be a potential treatment for fibrosis cataract in clinic.